Estimating Gaits of an Ancient Crocodile-Line Archosaur Through Trajectory Optimization, With Comparison to Fossil Trackways - Polet, Delyle T.; Hutchinson, John R. (Frontiers in Bioengineering and Biotechnology, 2022)
Fossil trackways provide a glimpse into the behaviour of extinct animals. However, while providing information of trackmaker size, stride and even speed, the actual gait of the organism can be ambiguous. This is especially true of quadrupedal animals, where disparate gaits can have similar trackway patterns. Here predictive simulation using trajectory optimization can help distinguish gaits used by trackmakers. First, we demonstrate that a planar, five-link quadrupedal biomechanical model can generate the qualitative trackway patterns made by domestic dogs, although a systematic error emerges in track phase (relative distance between ipsilateral pes and manus prints). Next, we use trackway dimensions as inputs to a model of Batrachotomus kupferzellensis, a long-limbed, crocodile-line archosaur (clade Pseudosuchia) from the Middle Triassic of Germany. We find energetically optimal gaits and compare their predicted track phases to those of fossil trackways of Isochirotherium and Brachychirotherium. The optimal results agree with trackways at slow speeds, but differ at faster speeds. However, all simulations point to a gait transition around a nondimensional speed of 0.4 and another at 1.0. The trackways likewise exhibit stark differences in track phase at these speeds. In all cases, including when simulations are constrained to fossil track phase, the optimal simulations after the first gait transition do not correspond to a trot, as often used by living crocodiles. Instead, they are a diagonal sequence gait similar to the slow tölt of Icelandic horses. This is the first evidence that extinct pseudosuchians may have exhibited different gaits than their modern relatives, and of a gait transition in an extinct pseudosuchian. The results of this analysis highlight areas where the models can be improved to generate more reliable predictions for fossil data, while also showcasing how simple models can generate insights about the behaviour of extinct animals.